The Place of Effective Planning and Organizational Resource in Manufacturing Firms in Perspective - Anthony Anyibuofu Kifordu; Asunday Ogala (RIRAI Publisher, 2020)
The research study takes a look at Effective Planning and Organizational resources on Productivity using manufacturing firms in Anambra state Nigeria as a case study. Two objectives were raised; to determine the significant difference between poor planning and organisational goals and to evaluate the significant difference between poor planning and attainment of target customers. The survey used spearman’s rank correlation coefficient to determine the various statistical relationships in the study. The results revealed that effective planning has a relationship with organizational productivity and that effective planning lead to employee’s performance in an organization. Therefore, the study concludes and recommends that managers time and attention is that of improving productivity in manufacturing firms which is very important for both survival and maintenance attaining goals of the firms, therefore the organizations should measure productivity on how well resources are combined and utilized to accomplish specific desirable results to be able to achieve its objectives on organizational need, articulate its strategies and carefully pursue them.